Enhancing the production of chlorophyll f in the cyanobacterium Synechocystis sp. PCC 6803 - Qi, Man; Taunt, Henry N; Bečková, Martina; Xia, Zhi; Trinugroho, Joko P; Komenda, Josef; Nixon, Peter J (Physiologia plantarum, 2025)
One potential approach to improve the productivity of cyanobacteria and microalgae is to enhance photosynthetic efficiency by introducing far-red absorbing pigment molecules (such as chlorophylls f and d) into the photosynthetic apparatus to expand the range of photosynthetically active radiation. We have shown previously that expressing the ChlF subunit of Chroococcidiopsis thermalis PCC 7203 in the model cyanobacterium Synechocystis sp. PCC 6803 (Syn6803) is sufficient to drive the production of chlorophyll f (Chl f), but only to low levels (0.24% Chl f/Chl a). By using the strong Pcpc560 promoter and an N-terminal truncated derivative of ChlF, we have been able to increase the yield of Chl f in white light by over 30-fold to about 8.2% Chl f/Chl a, close to the level displayed by far-red photoacclimated C. thermalis 7203. Additionally, we demonstrate that ChlF from Fisherella thermalis PCC 7521, like ChlF from C. thermalis 7203, assembles into a variant of the monomeric photosystem II (PSII) core complex termed the super-rogue PSII complex when expressed in Syn6803. This contrasts with the originally reported formation of a ChlF homodimeric complex in Synechococcus sp. PCC 7002. Overall, our work is an important starting point for mechanistic and structural studies of super-rogue PSII and for incorporating Chl f into the photosynthetic apparatus of Syn6803.
Keywords: Photosynthesis; bakteriální proteiny; Photosystem II Protein Complex; světlo; Synechocystis; Chlorophyll; chlorofyl; Light; Bacterial Proteins; fotosyntéza; fotosystém II (proteinový komplex)